IT SOMETIMES SPEAKS TO US - Manitowabi, Joshua (2017)
This thesis looks at ways of Anishinaabe cultural resurgence for Indigenous youth through our current education systems. Three Anishinaabe elders who had experience in Anishinaabe on-reserve schools and in community Indigenous education programs were interviewed to learn their views on what had worked and not worked in past attempts to integrate Anishinaabe language and cultural knowledge into curriculum and programming. Their views on curriculum content, pedagogical methods, and education policy were solicited to gain a better understanding of how to decolonize the current Eurocentric school system and provide more successful learning experiences for Anishinaabe children and youth. The key findings were: 1) language and spiritual education must be at the core of the curriculum; 2) elders’ knowledge and their oral stories and oral history had to be the key means of transferring knowledge to the younger generation; 3) land-based, hands-on experiential learning experiences that utilized the knowledge and skills of community members were essential to successfully engaging students in the learning process; 4) teachers needed to take responsibility for identifying and nurturing the learning spirit in each child; and 5) commitment from the government for adequate funding, support resources and class time was essential for the successful integration of Anishinaabe language and cultural knowledge into on-reserve school systems. Thesis Master of Arts (MA) This thesis examines the insights of three Anishinaabe elders (knowledge holders) who had extensive experience in Anishinaabe on-reserve schools or in community Indigenous education programs. They were interviewed to learn their views on what had and had not worked in past attempts to integrate Anishinaabe language and cultural knowledge into on-reserve schools and programming. Their insights inform recommendations for five strategies to improve the engagement of Anishinaabe students through culture-based teachings.